Free Feeding of CpG-Oligodeoxynucleotide Particles Prophylactically Attenuates Allergic Airway Inflammation and Hyperresponsiveness in Mice - Okajima, Takuma; Shigemori, Suguru; Namai, Fu; Ogita, Tasuku; Sato, Takashi; Shimosato, Takeshi (Frontiers in Immunology, 2021)
CpG-oligodeoxynucleotides (CpG-ODNs) constitute an attractive alternative for asthma treatment. However, very little evidence is available from studies on the oral administration of CpG-ODNs in animals. Previously, we developed acid-resistant particles (named ODNcap) as an oral delivery device for ODNs. Here, we showed that free feeding of an ODNcap-containing feed prophylactically attenuates allergic airway inflammation, hyperresponsiveness, and goblet cell hyperplasia in an ovalbumin-induced asthma model. Using transcriptomics-driven approaches, we demonstrated that injury of pulmonary vein cardiomyocytes accompanies allergen inhalation challenge, but is inhibited by ODNcap feeding. We also showed the participation of an airway antimicrobial peptide (Reg3γ) and fecal microbiota in the ODNcap-mediated effects. Collectively, our findings suggest that daily oral ingestion of ODNcap may provide preventive effects on allergic bronchopulmonary insults via regulation of mechanisms involved in the gut-lung connection.